How to Count Speed? Utilizing Android Applications to Support a Concept Attainment Model to Help Mathematical Thinking Skills - Abidin, Zaenal; Herman, Tatang; Wahyudin, W.; Wiryanto, W.; Farokhah, Laely; Penehafo, Amadhila Elina (Universitas Pendidikan Indonesia (UPI), 2024)
Examining and explaining the mathematical thinking skills of primary school students who employed an Android app as a concept attainment technique was the aim of this study. The inquiry used a 3 x 2 factorial design and a quantitative methodology. The study included twenty-eight fifth-grade students from two different courses. The results showed that students' mathematical thinking skills differed between those taught using a conventional strategy and those taught using a concept attainment method using an Android app and digital comic. Different mathematical thinking abilities are shown by students with levels of self-efficacy, according to the other research. This is because, in comparison to students in other groups, students with high levels of self-efficacy have more prior knowledge. Ultimate result shows no relationship between developing mathematical thinking skills and self-efficacy. This study could help educate people about various educational programs and media that can be used to enhance their capacity for mathematical thinking.